PLIOCENE ARCTIC TEMPERATURE CONSTRAINTS FROM THE GROWTH RINGS AND ISOTOPIC COMPOSITION OF FOSSIL LARCH - Ballantyne A.P.; Baker P.A.; Rybczynski N.; Harington C.R.; White D. (My University, 2006)
Instrumental records reveal that the current rate of Arctic warming greatly exceeds mean global warming. However, Arctic temperatures during the Pliocene were considerably warmer than present, making it an excellent time period for investigating potential consequences of current warming trends. Here we focus on an early Pliocene (4 to 5 Ma) peat deposit from Ellesmere Island, characterized by a remarkable fossil assemblage representative of a modern boreal forest. Among the fossils are well-preserved samples of an extinct larch (Larix groenlandii), which were exploited as an archive of paleoclimatic information. We reconstruct Pliocene terrestrial temperatures in the high Arctic using a novel approach that combines measurements of ring-width and oxygen isotopes. This technique was calibrated by analyzing modern analog larch growing at the northern extent of their range and accounting for biotic fractionation of oxygen isotopes using a global database of modern trees. Based on this approach, we estimated mean annual temperature in the Arctic during the Pliocene to be - 5.5 ± 1.9 °C, indicating that Arctic temperatures were 14.2 °C warmer than today. This more precise multi-proxy estimate is slightly warmer than previous estimates derived from empirical evidence and general circulation models. Our results also demonstrate that the biotic fractionation of oxygen isotopes in cellulose is non-linear and dependent upon regional factors affecting aridity, such as latitude and elevation. Therefore the simultaneous measurement of oxygen isotopes and morphological characteristics in paleovegetation can be useful in constraining climatic variables of Earth's past. © 2006 Elsevier B.V. All rights reserved.
Keywords: FOSSIL WOOD; ISOTOPES; MULTI-PROXY; PALEOCLIMATE; PLIOCENE; TEMPERATURE; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен